2006
DOI: 10.1002/hep.21075
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic insights into the hepatoprotective role of N-acetylcysteine in mouse liver

Abstract: The hepatoprotective mechanisms of N-acetylcysteine (NAC) in non-acetaminophen-induced liver injury have not been studied in detail. We investigated the possibility that NAC could affect key pathways of hepatocellular metabolism with or without changes in glutathione (GSH) synthesis. Hepatocellular metabolites and high-energy phosphates were quantified from mouse liver extracts by 1 H-and 31 P-NMR (nuclear magnetic resonance) spectroscopy. 13 C-NMR-isotopomer analysis was used to measure [U-13 C]glucose metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 37 publications
5
73
0
1
Order By: Relevance
“…Indeed, previous research has suggested that NAC does not scavenge NAPQI and therefore cannot prevent the initial phase. Rather, NAC hepatoprotection might involve an alternative mechanism that impacts the toxic phase, e.g., free radical trapping, increased GSH synthesis, or enhanced mitochondrial energy production (Lauterburg et al, 1983;Corcoran et al, 1985b;reviewed in De Flora et al, 2001;Zwingmann and Bilodeau, 2006;Saito et al, 2010). Our observation that i.p.…”
Section: Acetylcyclopentanone Prevents Acetaminophen Hepatotoxicitymentioning
confidence: 73%
“…Indeed, previous research has suggested that NAC does not scavenge NAPQI and therefore cannot prevent the initial phase. Rather, NAC hepatoprotection might involve an alternative mechanism that impacts the toxic phase, e.g., free radical trapping, increased GSH synthesis, or enhanced mitochondrial energy production (Lauterburg et al, 1983;Corcoran et al, 1985b;reviewed in De Flora et al, 2001;Zwingmann and Bilodeau, 2006;Saito et al, 2010). Our observation that i.p.…”
Section: Acetylcyclopentanone Prevents Acetaminophen Hepatotoxicitymentioning
confidence: 73%
“…5), because the relatively low concentration of the active species (thiolate) would consequentially limit electrophile scavenging. In fact, there is evidence that NAC cytoprotection involves an indirect mechanism that is not based on electrophile scavenging, for example, increased GSH synthesis or mitochondrial bioenergetics (Zwingmann and Bilodeau, 2006;Jaeschke and Woolbright, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…NAC is a comparatively safe drug for APAP-induced liver injury (AILI) and is currently being used to treat acute viral hepatitis and other acute hepatic failures (10). However, some studies show that a prolonged treatment with a high dose of NAC (600 to 1200 mg/kg per day) interferes with the normal hepatic mitochondrial metabolic processes and impairs liver regeneration after AILI by interrupting nuclear factor (NF)-jB signal pathways (22,34,37). Although there have been numerous studies on the detailed mechanisms of action of the effect of NAC on APAP toxicity, a new generation of drugs with improved efficacy and decreased interruption of normal hepatic function should be developed.…”
Section: Introductionmentioning
confidence: 99%